The association of vitamin D with semen quality and fertility hormones in idiopathic recurrent pregnancy loss without the female factor - Şahin, Banuhan; Alataş, Erkan (Journal of Surgery and Medicine, 2021)
Background/Aim: There is a lack of data about male contribution to idiopathic recurrent pregnancy loss (IRPL). The study aimed to investigate the factors associated with males, including Vitamin D, semen parameters, fertility hormones, and some demographical features in IRPL. Methods: In this cross-sectional study, the data of 41 men whose partners were diagnosed with recurrent pregnancy loss between February 2014 to February 2015 were collected. Female partners were examined fully, including thrombophilia factors, and no cause was detected. The karyotypes of both partners were normal. Men’s 25-hydroxy-vitamin D (25-OH-VD) levels, semen parameters (ejaculate volume, total sperm count per ejaculate, sperm concentration, sperm progressive motility, and sperm morphology), and fertility hormones (follicle-stimulating hormone, luteinizing hormone, total testosterone, estradiol, and prolactin) were assessed. Results: Mean 25-OH-VD was lower (18.4 (9.6) ng/ml) than the normal range. We found that testosterone was significantly lower in the group with 25-OH-VD ≤19 ng/dl when compared to the group with 25-OH-VD ≥20 ng/ml. There is a positive correlation between 25-OH-VD and testosterone levels. Although it was not statistically significant, there was a tendency for decreased sperm morphology. Conclusion: Serum testosterone levels of men whose partners were diagnosed with IRPL decreased with lower 25-OH-VD levels. In addition to standard female factors, male factors should also be taken into consideration when evaluating the risk of IRPL.